Electrocardiographic predictors of successful resynchronization of left bundle branch block by His bundle pacing - Arnold, Ahran D.; Shun‐Shin, Matthew J.; Keene, Daniel; Howard, James P.; Chow, Ji‐Jian; Lim, Elaine; Lampridou, Smaragda; Miyazawa, Alejandra A.; Muthumala, Amal; Tanner, Mark; Qureshi, Norman A.; Lefroy, David C.; et al. (Journal of cardiovascular electrophysiology, 2021)
Background His bundle pacing (HBP) is an alternative to biventricular pacing (BVP) for delivering cardiac resynchronization therapy (CRT) in patients with heart failure and left bundle branch block (LBBB). It is not known whether ventricular activation times and patterns achieved by HBP are equivalent to intact conduction systems and not all patients with LBBB are resynchronized by HBP. Objective To compare activation times and patterns of His‐CRT with BVP‐CRT, LBBB and intact conduction systems. Methods In patients with LBBB, noninvasive epicardial mapping (ECG imaging) was performed during BVP and temporary HBP. Intrinsic activation was mapped in all subjects. Left ventricular activation times (LVAT) were measured and epicardial propagation mapping (EPM) was performed, to visualize epicardial wavefronts. Normal activation pattern and a normal LVAT range were determined from normal subjects. Results Forty‐five patients were included, 24 with LBBB and LV impairment, and 21 with normal 12‐lead ECG and LV function. In 87.5% of patients with LBBB, His‐CRT successfully shortened LVAT by ≥10 ms. In 33.3%, His‐CRT resulted in complete ventricular resynchronization, with activation times and patterns indistinguishable from normal subjects. EPM identified propagation discontinuity artifacts in 83% of patients with LBBB. This was the best predictor of whether successful resynchronization was achieved by HBP (logarithmic odds ratio, 2.19; 95% confidence interval, 0.07–4.31; p = .04). Conclusion Noninvasive electrocardiographic mapping appears to identify patients whose LBBB can be resynchronized by HBP. In contrast to BVP, His‐CRT may deliver the maximum potential ventricular resynchronization, returning activation times, and patterns to those seen in normal hearts.